THE MAIN CRITERIA FOR DEVELOPING A SYSTEM OF VALUES IN THE TRAINING OF FUTURE HISTORY TEACHERS (International Conference on Economics, Finance, Banking and Management, 2024)
The article explores the multifaceted process of fostering value systems in future history teachers, emphasizing the integration of personal and professional qualities. It highlights the significance of cultural, spiritual, and national factors in shaping educators' ethical and moral worldview. The study identifies essential criteria for value formation, such as informational-cognitive, personal-value, emotional, and activity-creative aspects, and provides detailed indicators for each. The research also categorizes levels of national pride among university students and outlines the theoretical and practical implications of value-oriented education. This work underscores the importance of harmonizing national traditions, cultural heritage, and professional competencies to prepare morally and intellectually mature educators capable of contributing to society's development.